An Institutional Survey to Assess and Create Awareness of Inter-dental Cleaning Aids among the Patients Visiting a Dental Hospital in Ahmedabad - Jinay D. Sathwara; Ashish Kaur Chaudhary; Eshita Patel; Hiral Akshat Parikh; Sirsha Bhattacharjee; Rajat Gajjar; Dhaval Niranjan Mehta (Wolters Kluwer Medknow Publications, 2024)
Objectives: To assess and evaluate the knowledge, awareness, and usage of inter-dental aids among the patients visiting a dental hospital. Materials and Methods: A cross-sectional descriptive study was conducted among patients using a questionnaire for evaluation of routine oral hygiene regimens. Results: 89% of patients brush their teeth only once a day. 77% of patients do not use any inter-dental aid, while 76% of patients are unaware about inter-dental aids. Conclusion: A very small part of the population is aware about the importance of using inter-dental aids in maintaining proper oral hygiene. Dentists play a key role in educating the society and encouraging them to use other aids apart from toothbrushes to prevent oral diseases.